Experimental model of multidetector device based on CdZnTe detectors - Batiy, V.G.; Nenakhov, A.N.; Pravdiviy, A.A.; Kochnev, N.A.; Selyukova, V.V.; Khazhmuradov, M.A. (Вопросы атомной науки и техники, 2005)
The multidetector device for measurement of angular distributions of intensity of gamma - radiation is described. Results of tests of experimental model of device are presented and prospects of use of such device are shown.